Imprints of miRNA- An Update (Indian Journal of Forensic Medicine & Toxicology, 2021)
Introduction: Micro Ribonucleic acid (miRNA) is the novel fraction of non-coding RNA, which is considered as the biological measure of genetic state of a cell. It plays a mantle regulatory role post transcriptionally, involving both biological and pathologic cellular processes. miRNAs possess unique properties like, abundant tissue expression which allows for reproducible isolation and quantification. Methods: Literature search was carried out by using different combinations of keywords on Pub Med and Cochrane database to retrieve the data for the literature review. Discussion: Distinct expression profiles of miRNA in OSCC (Oral Squamous Cell Carcinoma) offers the use of specific miRNAs signature for early-stage diagnosis, prediction and prognosis. It plays a critical role in the initiation and progression of cancer functioning either as an oncogene or as tumor suppressor. At present, it has a huge impact on understanding the aberrant gene modifications in OSCC and its future effects on prognosis and therapeutic relevance needs to be looked upon.Conclusion: Distinct phases of miRNA from its origin, properties, functionality, detection, cancer association to future trends are updated in this review.
Keywords: miRNA, MicroRNA, Profiling, Biomarker, Oral cancer